SANZ ORO, R. (2001). "Orientación psicopedagógica y calidad educativa". Madrid: Pirámide. 280 págs. - Rufino Cano González (Universidad de La Rioja, 2013)
SANZ ORO, R. (2001). Orientación psicopedagógica y calidad educativa. Madrid: Pirámide. 280 págs.